Effectiveness of Redd+ Implementation Through FCPF-Cf on Welfare in Teluk Sulaiman - Farros Syahin Fadhil Al Mukhaimin; Khoirul Amin; Mohammad Dziqie Aulia Al Farauqi (PT Keberlanjutan Strategis Indonesia, 2026)
This study checks how well REDD+ and FCPF efforts worked in supporting lasting growth and boosting local living conditions at Teluk Sulaimaun. It looks into shifts in tree coverage, how involved villagers were, along with changes in family income and jobs. We combined several ways to gather info - talking to 150 household leaders, holding detailed talks with main players, also going through existing project records. Results suggest forest loss dropped by 23% in five years,whereas typical home earnings rose 7%, thanks to new work options like beekeeping or nature tours. Still, a few hurdles popped up - like uneven gains across groups, poor teamwork between sectors, or low skill levels within communities. The research wraps up by saying carbon projects work best when everyone’s included from the start, rewards are shared openly, while local systems keep getting stronger over time.